2007
DOI: 10.1080/10888430709336632
|View full text |Cite
|
Sign up to set email alerts
|

Components of Reading Ability: Multivariate Evidence for a Convergent Skills Model of Reading Development

Abstract: Elementary and middle school children were given a large battery of tests evaluating reading subskills and reading-related cognitive abilities. These measures were used to define latent constructs representing skills and abilities believed to be important components of reading comprehension. Hypothesized relationships among these constructs were specified within the context of a structural model we call the "Convergent Skills Model of Reading Development," and developmental differences in the relative contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
230
3
15

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(279 citation statements)
references
References 24 publications
31
230
3
15
Order By: Relevance
“…In the whole sample inhibitory control was weakly but positively correlated with both decoding and comprehension abilities. Decoding and comprehension were also positively and substantially correlated to each other, what is in line with findings of other studies (e.g., Conners & Olson, 1990;Vellutino et al, 2007).…”
Section: Inhibitory Control and Reading Skill In Relation To Child's supporting
confidence: 81%
See 2 more Smart Citations
“…In the whole sample inhibitory control was weakly but positively correlated with both decoding and comprehension abilities. Decoding and comprehension were also positively and substantially correlated to each other, what is in line with findings of other studies (e.g., Conners & Olson, 1990;Vellutino et al, 2007).…”
Section: Inhibitory Control and Reading Skill In Relation To Child's supporting
confidence: 81%
“…Moreover, in the last 30 years much effort was done to decompose reading competence. Phonemic awareness, spelling competence, grammar, working memory, phonological decoding or understanding are just some of the those broadly described in the literature (e.g., Borowsky & Besner, 2006;Hoover & Gough, 1990;Perfetti, 2001;Vellutino, Tunmer, Jaccard, & Chen, 2007). Such a large number of factors creates methodological difficulties, therefore in recent years a new trend in the research field has emerged.…”
Section: Reading Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is critical to produce accurate models of the development of reading comprehension in order to develop evidence-based curricula and interventions for young and struggling readers. However, reading comprehension is determined by a wide range of component skills and processes Oakhill and Cain 2011;Vellutino et al 2007), making the specification of such models a challenge. In this paper, we evaluate one highly influential model, the Simple View of Reading (SVR), which offers a relatively simple framework within which to conceptualise reading comprehension (Gough and Educ Psychol Rev (2011) 23:553-576 …”
mentioning
confidence: 99%
“…The empirical support for the Simple View in typically developing children is extensive (Catts, Herrera, Nielsen, & Bridges, 2015;Hulme & Snowling, 2014;Language and Reading Research Consortium, 2015;Ripoll Salceda et al, 2014), and the model has also been suggested to be useful as a theoretical framework for reading in deaf children (Chamberlain & Mayberry, 2000;Stone et al, 2015). At the same time, it has been suggested that more detailed specification of the cognitive mechanisms involved in the two components of the Simple View would promote greater understanding of reading development (Hulme & Snowling, 2014;Kirby & Savage, 2008;Stuart, Stainthorp, & Snowling, 2008), and attempts have been made to achieve this (e.g., Byrne et al, 2013;Kim & Phillips, 2014;Kim, 2015aKim, , 2015bTunmer & Chapman, 2012;Vellutino, Tunmer, Jaccard, & Chen, 2007).…”
Section: Learning To Comprehend Texts As a Sign Language Usermentioning
confidence: 99%